Pemanfaatan Hypnoteaching dalam Mengajarkan Keterampilan Kewirausahaan dan Ekonomi di SDN Kadumekar Babakancikao Purwakarta - Jalaludin Jalaludin; Gugun Rohmat Tul Hidayat; Amellia Aztiannisa Dewi; Resa Nur Azizah (STIE Syariah Indonesia Purwakarta, 2026)
Based on the results of observations, the PKM team found several unique phenomena related to the utilization of hypnoteaching in teaching entrepreneurship and economic skills at SDN Kadumekar, one of which is that many people are still taboo against hypnoteaching, there are still many schools that teach traditional methods, teachers and student guardians are still limited in improving teaching skills, and there are still few people who know the effectiveness of hypnoteaching entrepreneurial skills and economic skills to students. The purpose of this PKM is to utilize hypnoteaching in teaching entrepreneurship and economic skills at SDN Kadumekar. This PKM method uses observation, socialization and discussion, monitoring, and evaluation. This PKM can be concluded that the level of understanding of respondents or PKM partners before and after the PKM implementation has changed quite drastically from the average value of 23.04 points in the category of very not understanding, changing drastically to 89.5 points in the category of very understanding. These results show that guardians and teachers at SDN Kadumekar are now more prepared to utilize hypnoteaching as part of entrepreneurship and economics learning, creating a more effective and enjoyable learning experience for students. In addition, through this PKM, teachers and student guardians already know the functions and benefits of hypnoteaching, the benefits of hypnoteaching in teaching entrepreneurial skills, how to form an entrepreneurial mindset in students, hypnoteaching techniques for student concentration, building a creative, innovative, and independent mindset in the future in students, the main characteristics of hypnoteaching-based teaching, how hypnoteaching improves students' economic skills, the first step in starting a hypnoteaching-based lesson, hypnoteaching to overcome fear, and learning economics with inspirational stories.